[Medicinal leeches and hirudotherapy]. - Gödekmerdan, Ahmet; Arusan, Suat; Bayar, Batu; Sa?lam, Naim (My University, 2011)
Leeches have been used in the treatment of certain diseases since ancient times. There are a few species of medicinal leeches. However, H. medicinalis and H. verbana are known in Turkey. Currently, Turkey is one of the world's most important leech-exporting countries. Secretion of the salivary glands of medical leeches contains more than 100 bioactive substances. These secretions include vasodilators, bacteriostatic, analgesic, anti-inflammatory and anticoagulants, anti-edematous, which eliminate microcirculatory disorders, restore the damaged vascular permeability of tissues and organs, eliminate hypoxia, reduce blood pressure, increase immune system activity, resolving the cause of pain and improve the bioenergetic status of the organism. U.S. Food and Drug Administration (Food and Drug Authority of USA-FDA) have allowed the sale of leeches in this country, the use for plastic surgery, the general purposes and microsurgery in 2004. Turkey is the richest source in terms of the medical leech. Better evaluation of this valuable commodity and more effective use of hirudotherapy in modern medical practice as supportive treatment is very important.
Tibbi sülükler ve hirudoterapi.
Keywords: Animals; Bloodletting; Hirudo medicinalis; Humans; Leeching; Salivary Glands; Turkey; animal; chemistry; Hirudo medicinalis; human; leeching; methodology; phlebotomy; physiology; review; salivary gland; secretion (process); Turkey (republic)